Analysis of the effect of autograft characteristics on the restoration of hemogram parameters and the need for hemotransfusions in oncohematological patients - N. V. Isaeva; N. A. Zorina; E. L. Nazarova; E. A. Poponina; F. S. Sherstnev (Сибирский научный медицинский журнал, 2025)
The aim of the study was to analyze the effect of autograft characteristics on the restoration of hemogram parameters and the need for hemotransfusions in oncohematological patients. Material and methods. The study included 118 patients with multiple myeloma, 23 with non-Hodgkin’s lymphomas, and 21 with Hodgkin’s lymphoma who underwent autologous hematopoietic stem cell transplantation. The number of live CD34+ cells in thawed autografts stored in liquid nitrogen in the presence of dimethyl sulfoxide was calculated, in addition, the number of viable nucleated cells was determined by testing with vital dye. The number of CD34+ cells in autografts stored in liquid nitrogen in the presence of dimethyl sulfoxide was calculated. The number of viable nucleated cells was determined by testing with a vital dye. The restoration of hematopoiesis after transplantation of autologous hematopoietic stem cells was assessed by the timing of compensation for neutropenia and thrombocytopenia, and the number of transfusions of platelet concentrate and erythrocyte-containing components in the posttransplantation period was taken into account. Results. With infusion of a dose of live CD34+ cells of more than 5×106 per kilogram of body weight in patients with multiple myeloma, a shorter period of neutropenia was observed, with non-Hodgkin’s lymphomas, a significant reduction in the duration of cytopenia and a decrease in the number of transfusions of erythrocyte–containing components were revealed, in all nosological groups – a decrease in the number of necessary transfusions of platelet concentrate. With the viability of nucleated cells in leukoconcentrates of more than 70 % in patients with non-Hodgkin’s lymphomas, a decrease in the timing of neutropenia and thrombocytopenia was found without significant intensification of transfusion therapy. Conclusions. The infusion of live CD34+ cells into oncohematological patients at a dose exceeding 5×106 per kilogram of body weight, with a viability of nucleated cells in leukoconcentrates exceeding 70 %, ensures a reduction in the duration of neutropenia and thrombocytopenia, as well as a decreased need for hemotransfusions during the early post-transplant period. The results obtained should be taken into account when planning the procurement and storage of autologous leukoconcentrates.